Philosophy of Communication and Umberto Eco's Infinity of Lists: The Interplay of the Poetic and Pragmatic. Issue 3 (27th May 2017) - Mancino, Susan
ABSTRACT: This article conceptualizes the importance of Umberto Eco's understanding of lists for philosophy of communication. Philosophy of communication is understood as the necessary and insightful interplay of the poetic and pragmatic through which meaning emerges. In The Infinity of Lists, Eco offers an essay-length interpretation of lists presented alongside a collection of art and literature that represent his theoretical work in action. Eco articulates lists as a means for cultural order and form in the attempt to convey what is otherwise beyond articulation. Although philosophers of communication have recognized the importance of Eco's philosophical and semiotic project for human communication, his work on lists has received little attention within and outside of the field of communication. This article assumes that lists are significant to Eco's project and to philosophy of communication, situated in the interplay of the poetic and the pragmatic.